A systematic review and meta‐analysis of basal microbiota and cognitive function in Alzheimer's disease: A potential target for treatment or a contributor to disease progression? - Ana Maria Jimenez‐García; Maria Villarino; Natalia Arias (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract A systematic review and meta‐analysis examined the impact of gut microbiota in Alzheimer's disease (AD) pathogenesis. Dysbiosis may influence neurodegeneration by affecting gut permeability and neurotrophic factors, leading to cognitive decline. The study analyzed microbiome differences between patients with AD and healthy individuals, as well as the impact of various interventions in both preclinical and clinical studies. Of 60 studies reviewed, 12 were excluded from the meta‐analysis due to unsuitable data or lack of control groups. Meta‐analyses revealed significant cognitive impairment in AD patients and animal models, with specific tests identifying these deficits. Notably, Bacteroides levels were higher in patients with AD, whereas probiotics improved Prevotella levels. Natural treatments increased Bacteroidetes and reduced Firmicutes in animal models. The findings emphasize the need for standardized methods to develop therapies targeting the gut microbiota to restore cognition in AD. Understanding individual dysbiosis could further clarify the cognitive effects of the gut–brain axis. Highlights Dysbiosis in the gut microbiota is linked to cognitive decline in Alzheimer's disease (AD). Patients with AD show significant differences in Bacteroides levels compared to healthy individuals. Probiotic treatments increase Prevotella levels in AD animal models. Natural agents boost Bacteroidetes and reduce Firmicutes in AD animal models. Human studies show no consistent effects of gut microbiota interventions on cognitive function in AD.